Primary conservative treatment PCL rupture in athletes - A. R. Zaripov; A. P. Afanasiev; N. E. Magnitskaya; M. S. Ryazantsev; A. N. Logvinov; D. O. Ilyin; Zh. Yu. Pilipson; A. V. Frolov; M. N. Maysigov; A. V. Korolev; F. L. Lazko; A. A. Akhpashev (Научно-практическая ревматология, 2022)
The purpose of this study: to evaluate the results of conservative treatment of isolated grade II and III PCL rupture in athletes.Materials and methods. The study included 36 patients who were athletes at a professional level, with isolated PCL rupture, and have been treated non-operative in the period from 2012 to 2020. The non-operative protocol of isolated lesions of the PCL involve, bracing with posterior leg support, rehabilitation program determined by the symptoms and physical signs.Results. After 2 years from injury, the average score on the Tegner scale was 9 (5–10) (p=0.42). 32 (89%) patients returned to the previous level of sports activity, the average score on the Tegner scale was 9 (7–10). The mean time to return to sports-specific training was 10.6 (4–27) weeks, and the mean time to return to full competitive sport was 16.4 (10–40) weeks. Conclusion. The non-operative management of isolated, Hughston grade II and III PCL injuries gives excellent functional outcomes with a high proportion returning to the same level of sport.